Survival Strategy Of Fraud Victim In Paulo Coelho's Eleven Minutes Novel: An Individual Psychological Perspective - Triutami, Fathonah Wahyu; , Dr. M. Thoyibi, M.S; , Mauly Halwat Hikmat, Ph. D (2014)
This research paper aims at knowing the survival strategy of fraud victim in Eleven Minutes novel by Paulo Coelho which is analyzed by using individual psychological. The objective of the research is to analyze the novel based on the structural elements of the novel and to analyze the novel based on individual psychological proposed by Alfred Adler. The type of this research is descriptive qualitative. Data of the research are taken from primary and secondary data. The primary data of the research is Eleven Minutes novel. The secondary data of the research are taken from books, other source and website that related to the study. The technique of collecting data are reading novel, clasifying the data, identifying the data that can be analyzed, taking note, and browsing to the internet. The method to analyze of this data is descriptive analysis. Based on structural elements of the novel, Paulo Coelho delivers a moral message that "the strategy of life is one of the element to survive and cope the problem of human life". Based on the individual psychological analysis, the author illustrates a psychological phenomenon which an individual should make every effort to cope with the problem of life. The psychological phenomenon is shown by the struggle of Maria to survive in Switzerland after as fraud victim. Maria uses her creativity to manage her strategy. She also arranges her striving for superiority to provides her inferiority feeling to create fictional finalism.